대답:
에 대한 #S_k (n) = sum_ {i = 0} ^ ni ^ k #
# S_1 (n) = (n (n + 1)) / 2 #
# S_2 (n) = 1 / 6n (1 + n) (1 + 2n) #
#S_3 (n) = ((n + 1) ^ 4- (n + 1) -6S_2 (n) -4S_1 (n)
설명:
우리는 가지고있다.
#sum_ {i = 0} ^ ni ^ 3 = sum_ {i = 0} ^ n (i + 1) ^ 3 - (n + 1) ^ 3 #
i = 0} ^ ni ^ 3 = sum_ {i = 0} ^ ni ^ 3 + 3sum_ {i = 0} ^ ni ^ 2 + 3sum_ {i = 0} ^ ni + sum_ {i = 0} ^ n 1- (n + 1) ^ 3 #
(n + 1) ^ 3 # 0 = 3sum_ {i = 0} ^ ni ^ 2 + 3sum_ {i = 0} ^ ni + sum_ {
해결을위한 #sum_ {i = 0} ^ n i ^ 2 #
#sum_ {i = 0} ^ ni ^ 2 = (n + 1) ^ 3 / 3- (n + 1) / 3-sum_ {i = 0}
그러나 #sum_ {i = 0} ^ n = ((n + 1) n) / 2 # 그래서
#sum_ {i = 0} ^ ni ^ 2 = (n + 1) ^ 3 / 3- (n + 1) / 3 - ((n + 1) n) / 2 #
#sum_ {i = 0} ^ ni ^ 2 = 1 / 6n (1 + n) (1 + 2n) #
동일한 절차를 사용하여 #sum_ {i = 0} ^ n i ^ 3 #
#sum_ {i = 0} ^ n ^ 4 = sum_ {i = 0} ^ n (i + 1) ^ 4 - (n + 1) ^ 4 #
#sum_ {i = 0} ^ ni ^ 4 = sum_ {i = 0} ^ ni ^ 4 + 4sum_ {i = 0} ^ ni ^ 3 + 6sum_ {i = 0} ^ ni ^ 2 + 4sum_ {i = 0 } ^ ni + sum_ {i = 0} ^ n 1- (n + 1) ^ 4 #
(0 + 1) ^ n + sum_ {i = 0} ^ n 1- (n + 1) ^ 2 = 4sum_ {i = 0} ^ ni ^ 3 + 6sum_ { 4 #
(n) + 4S_1 (n) + (n + 1) - (n + 1) ^ 4 #
해결을위한 # S_3 (n) #
#S_3 (n) = ((n + 1) ^ 4- (n + 1) -6S_2 (n) -4S_1 (n)
이리 #S_k (n) = sum_ {i = 0} ^ ni ^ k #